Condições De Produção De Textos E Reescrita Orientada Por Bilhetes - LISBOA, Jussara Regina de Souza (2011)
This work suggests issues related to production conditions and the rewriting of texts geared for tickets, at school, such questions are found in the productions of elementary school students. My goal is to analyze what are the interferences that such conditions of textual production, carry on writing and the role they play in guiding the tickets rewrite these students. Study subjects are teachers and students. The students were enrolled at the time the 9th grade of elementary school. A teacher and a teacher worked at the time, the effective teacher and researcher. The generation of data was in late 2009, the months of November and December. Procedures of analysis, qualitative methods have been developed which was the basic element of Evidential Paradigm Ginszburg (1989 and 1990) for its recovery in the uniqueness of this data and research is focused on finding the evidence. Hypotheses have been raised that conducted the investigation. The stay in school enabled me to collect the textual productions, collecting the materials used in the classes of text production; record seven classes for the production work and rewriting of texts, make notes in field diaries; enforce a semistructured interview with the teacher and an exploratory questionnaire to students. The look that guides this theoretical research is centered on language in place and the interaction between subjects, advocated by Bakhtin (2003, 2006). Among other scholars who depart this same look and fields like Textual Linguistics and Discourse Analysis, it has been Foucault (2002), Geraldi (1997, 2001, 2004, 2006), Indursky (2006), Koch (2004, 2006, 2006a, 2006b, 2007, 2007a, 2007b), Orlandi (2006, 2007, 2007a, 2008, 2008a), Pêcheaux (1997) and Ruiz (2001) whose investigations cut across the paths of language, text and discourse in its relation to teaching and learning of English. This research is justified by the need to better understand the conditions of textual production-oriented and rewriting tickets, as well as its role in the formation of Bullies in the public schools. The conclusions point to the need to create conditions for production of the text for students to recognize themselves as subjects of speech, thus recognizing the social character of language.